Intersections of Fibrodysplasia Ossificans Progressiva and Traumatic Heterotopic Ossification - Conan Juan; Alec C. Bancroft; Ji Hae Choi; Johanna H. Nunez; Chase A. Pagani; Yen-Sheng Lin; Edward C. Hsiao; Benjamin Levi (Biomolecules, 2024)
Heterotopic ossification (HO) is a debilitating pathology where ectopic bone develops in areas of soft tissue. HO can develop as a consequence of traumatic insult or as a result of dysregulated osteogenic signaling, as in the case of the orphan disease fibrodysplasia ossificans progressiva (FOP). Traumatic HO (tHO) formation is mediated by the complex interplay of signaling between progenitor, inflammatory, and nerve cells, among others, making it a challenging process to understand. Research into the pathogenesis of genetically mediated HO (gHO) in FOP has established a pathway involving uninhibited activin-like kinase 2 receptor (ALK2) signaling that leads to downstream osteogenesis. Current methods of diagnosis and treatment lag behind pre-mature HO detection and progressive HO accumulation, resulting in irreversible decreases in range of motion and chronic pain for patients. As such, it is necessary to draw on advancements made in the study of tHO and gHO to better diagnose, comprehend, prevent, and treat both.